Double sequential defibrillation therapy for out-of-hospital cardiac arrests: The London experience. (August 2017) - Emmerson, Amber C.; Whitbread, Mark; Fothergill, Rachael T.
Abstract: Background: Despite advances in treatment for out-of-hospital cardiac arrest (OHCA), a subgroup of patients remain in refractory ventricular fibrillation (RVF) during resuscitation. Recent evidence suggests that double sequential defibrillation (DSD), where two shocks are delivered to the patient in quick succession, may provide an effective therapy for RVF. This study describes the characteristics and survival outcomes of OHCA patients treated by ambulance clinicians using a local DSD protocol in an attempt to resolve RVF. Methods: This is a retrospective, observational analysis of patients who received DSD by the London Ambulance Service from 1st July 2015 to 31st December 2016. A comparator group of patients who received more than six consecutive standard shocks (not DSD) for persistent VF was also identified. Outcomes included pre-hospital return of spontaneous circulation (ROSC), ROSC sustained to hospital, and survival to hospital discharge. DSD patients who survived to hospital discharge are reported in further detail. Results: During the 18-month study period, 45 patients were treated with DSD: a third obtained a pre-hospital ROSC and 7% survived to hospital discharge. We observed similar ROSC and survival rates amongst those who received standard defibrillation only. Conclusion: Our observational study did not find any clear benefit of DSD use by EMS in the treatment of RVF. However, we find that 3 patients, who were treated with DSD following unsuccessful single shocks, had their VF terminated. Prospective randomised clinical trials are urgently needed to investigate the potential value of DSD in the pre-hospital setting.